Developing a medical academic word list in English: A comparative analysis of vocabulary across medical sub-corpora / Anis Ashraf Zadeh - Anis Ashraf, Zadeh (2018)
This corpus-based lexical study presents the most frequently used medical academic vocabulary across a wide range of medical textbooks to fill the research gap in Wang’s et al. (2008) study in developing a medical academic word list based on research articles. The Medical Academic Word List of Textbooks (MAWLOT) was compiled from the Medical Academic Corpus of 3.5 million running words in written medical textbooks by examining the range and frequency of words outside the first 2,000 most frequently occurring words of English (GSL) (West, 1953) and the Academic Word List (AWL) (Coxhead, 2000). MAWLOT contains 459 word families which account for 11.27% of the vocabulary of the Medical Academic Corpus of the study. This good coverage of the MAWLOT provides evidence for teachers and learners in English for Academic Purposes (EAP) and English for Medical Purposes (EMP) to recognize which words are valuable to teach and learn. In addition, concordance lists of the most frequent collocations of the words included in the MAWLOT were provided for studying the words in multiple contexts to observe their behaviours with a greater number of word encounters. MAWLOT is the result of a corpus-based lexical study which, according to Coxhead (2000), “create[s] lists, concordances or data regarding the clustering of linguistic items in coherent, purposeful texts” (p. 227) to provide a useful basis for teachers and learners to set goals in their teaching and learning vocabulary in EAP and EMP. According to Bennett (2010), providing the best possible instruction for students is a desire of many instructors, which is achievable by using corpus linguistics in classrooms. One of the major results of corpus-based studies is developing a wordlist in a specific discipline to help students to practice the frequently used words of the discipline in everyday classrooms (Coxhead, 2010). Offering the first medical academic word list based on the textbooks besides their collocation/phraseological patterns, as well as an extra list of technical words in medicine (53 words) are the main results of the present study to help medical students fulfil their vocabulary needs in reading medical textbooks written in English.